A Prickly Love Story - Wheeler, Lisa; 1963-; Bynum, Janie (Boston, 2002)
After a series of rejections, a lonely porcupine finds true love with a prickly hedgehog.
"Megan Tingley books."
Keywords: Porcupines; Fiction; Hedgehogs; Fiction